2019
DOI: 10.1111/jonm.12883
|View full text |Cite
|
Sign up to set email alerts
|

Integrative review of studies about nurses who have been disciplined by their professional regulatory bodies

Abstract: Aim To synthesize knowledge in studies about nurses who had been disciplined by their professional regulatory bodies. Background Unprofessional conduct that violates patient safety, nursing standards or legislation can result in disciplinary action that affects nurse's professional rights to practice. However, research on disciplinary procedures in nursing is fragmented. Methods An integrative review was carried out with systematic searches between January 2006 and November 2018, using the CINAHL, PubMed, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…22,25 Based on previous research, nurses ' unprofessional conduct has been rarely studied at a national regulatory level. 26 Regardless of the number of nurses a country has, the percentage of nurses that face disciplinary cases is quite similar. For example, in the United States, 0.2% of nurses from 1996 to 2006 were investigated at the highest level, 27 in one Canadian province, less than 0.5% of nurses were disciplined from 2007 to 2017 28 and the percentage was similar in Israel (0.24%) from 2002 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…22,25 Based on previous research, nurses ' unprofessional conduct has been rarely studied at a national regulatory level. 26 Regardless of the number of nurses a country has, the percentage of nurses that face disciplinary cases is quite similar. For example, in the United States, 0.2% of nurses from 1996 to 2006 were investigated at the highest level, 27 in one Canadian province, less than 0.5% of nurses were disciplined from 2007 to 2017 28 and the percentage was similar in Israel (0.24%) from 2002 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…42,43,45,46,103 Two studies assessed effectiveness of penalties on rates of reoffending. 27,65 Most papers studied penalties as a whole, commenting on the most and least commonly applied penalties in the sample, [13][14][15][16][17][18][19]24,28,29,31,32,34,36,37,40,41,[47][48][49][50]57,[61][62][63]65,69,70,72,74,[76][77][78]80,82,84,88,93,98,[101][102][103]106,108,…”
Section: Common Reasons For Disciplinary Actionmentioning
confidence: 99%
“…One study reported an average of 12 years in practice before rst discipline, 61 another study reported that 60% of nurses were disciplined within the rst 10 years of practice, 111 and a review article also found an average of 12-14 years before rst discipline. 88 One study reported that nurses usually had more than six years' experience but had also recently changed employment or practice area within a year of the incident leading to disciplinary action. 48 Practice specialty Forty-two of 108 papers (39%) included practice specialty as a risk for disciplinary action.…”
Section: Common Reasons For Disciplinary Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…First is the need to link the business results of enterprises with the personal income of rural professional managers. This kind of behavior has short-term incentive effect [13]. This kind of mechanism is mainly to directly link the personal income of rural professional managers with their work performance, which can strengthen the work enthusiasm and management effect of rural managers.…”
Section: Incentive and Restraint Mechanismmentioning
confidence: 99%